Polycrystalline BiCuSeO oxide as a potential thermoelectric material - Li, Fu; Li, Jing-Feng; Zhao, Li-Dong; Xiang, Kai; Liu, Yong; Zhang, Bo-Ping; Lin, Yuan-Hua; Nan, Ce-Wen; Zhu, Hong-Min (Energy & environmental science, 2012)
This work revealed that BiCuSeO oxyselenide is a potential oxide-based thermoelectric material, whose dimensionless figure of merit ( ZT ) reaches ∼0.70 at 773 K. High phase-purity BiCuSeO polycrystalline materials with fine grains were synthesized by a facile method combining a solid-state reaction and spark plasma sintering. Purifying the constitutive phase and reducing the grain sizes by introducing a high-energy ball milling process before spark plasma sintering were found to be effective in property enhancement. The resultant single-phased BiCuSeO sample derived from ball-milled powders shows good electrical conductivity above 4.0 × 10 3 S m −1 and a large Seebeck coefficient above 200 μV K −1 . This compound has a low thermal conductivity (∼0.5 W m −1 K −1 ), which is associated with its low phonon transport speed and Young's modulus. Results indicated that BiCuSeO-based materials are promising for energy conversion applications in the moderate temperature range. Good electrical conductivity, large Seebeck coefficients and low thermal conductivity were obtained for pristine BiCuSeO oxides with a layered structure of alternately stacked conductive (Cu 2 Se 2 ) 2− and insulating (Bi 2 O 2 ) 2+ layers, resulting in a high ZT value of 0.70 at 773 K.